Othello - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Shakespeare made easy., 2002)
Presents the original text of Shakespeare's play side by side with a modern version. Includes a section with discussion questions and quizzes for students. Shakespeare's tragedy of the Moor whose love for Desdemona is destroyed by jealousy unfolds in easy-to-follow English as we speak it today. Othello's passion and Iago's treachery become clear in this straightforward modern version. The complete original text is laid out side-by-side with a complete modern translation. You'll find this book ideal for instant reference and understanding, whether you are reading Shakespeare for pleasure or studying for an exam.